2004
DOI: 10.1152/ajpheart.01131.2003
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations of heart rate and respiration synchronize during poetry recitation

Abstract: of heart rate and respiration synchronize during poetry recitation. Am J Physiol Heart Circ Physiol 287: H579 -H587, 2004. First published April 8, 2004 10.1152/ajpheart.01131.2003.-The objective of this study was to investigate the synchronization between low-frequency breathing patterns and respiratory sinus arrhythmia (RSA) of heart rate during guided recitation of poetry, i.e., recitation of hexameter verse from ancient Greek literature performed in a therapeutic setting. Twenty healthy volunteers perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 42 publications
4
67
0
1
Order By: Relevance
“…It is well known [23][24][25][45][46][47][48]51,52 that the phase of respiration influences the peripheral autonomic nervous system's outflow to the heart. However, till now it has never been shown when exactly this happens inside the cardiac cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known [23][24][25][45][46][47][48]51,52 that the phase of respiration influences the peripheral autonomic nervous system's outflow to the heart. However, till now it has never been shown when exactly this happens inside the cardiac cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Description of cardiorespiratory interaction in terms of coupling functions yields a new technique for the quantification of respiratory-related HRV. HRV is one of the central tools of psychophysiology and behavioural medicine 44 , and the respiratory component is a significant part of it [23][24][25][45][46][47][48] , representing mainly the vagal or parasympathetic part of the autonomic nervous system influences. Having introduced the time-continuous phase of the ECG, we obtain a continuous description of the HRV via the instantaneous frequency _ j e ðtÞ, instead of the commonly used discontinuous beat-to-beat description.…”
Section: Es Ps Eps Egmentioning
confidence: 99%
“…These fluctuations are forced to merge at the rate of respiration and to increase greatly in amplitude-enhancing measures of HRV and BRS [14,[40][41][42][43][44]. Breathing rate as slow as the 6 breaths/minute used in this study can be obtained by a paced respiration, a rhythmic speech, recitation of some poetry, rosary prayer, or yoga mantras [40][41][42][43][44]. As reported by Cysarz et al [43], the guided recitation of hexameter verse poetry exerts a strong influence on respiratory sinus arrhythmia by a prominent low-frequency component in the breathing pattern, generating a strong cardiorespiratory synchronization.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we showed that guided rhythmic speech exercises in the context of arts speech therapy (AST) cause changes in heart rate variability [1,2], cardiorespiratory interactions [3], as well as hemodynamics and oxygenation in the brain and muscle [4][5][6]. In particular, we demonstrated that during speech exercises, a decrease in cerebral hemodynamics and oxygenation occurred.…”
Section: Introductionmentioning
confidence: 92%